2013
DOI: 10.1186/1746-1596-8-111
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of chromatin remodeler DAXX in high grade urothelial carcinoma

Abstract: Background/AimsThe chromatin remodeler DAXX, a predominantly nuclear protein, regulates the status of chromatin organization. The aim of this exploratory immunohistochemical study was to evaluate DAXX protein expression in high grade invasive urothelial carcinoma (UC) of the bladder as a biological regulator of aggressiveness.MethodsQuantitative analysis was made on DAXX immunostained nuclei in tissue sections from 5 cases of bladder normal urothelium (NU) and 5 cases of bladder pT1 UC. Carcinoma in situ (CIS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Adenovirus(Ad) E1B-55kd protein can also interact with Daxx and break the colocalization of Daxx and PML within PML-NBs [ 17 ], so affect the transcription inhibitory activities of Daxx and its other functions [ 18 ]. It was shown that the protein expression of chromatin remodeler Daxx in high grade invasive urothelial carcinoma of the bladder and in its preinvasive phases changed through quantitative immunohistochemical analysis [ 19 ]. Which effects have Daxx in the progress of cervical cancer induced by HR-HPVs?…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus(Ad) E1B-55kd protein can also interact with Daxx and break the colocalization of Daxx and PML within PML-NBs [ 17 ], so affect the transcription inhibitory activities of Daxx and its other functions [ 18 ]. It was shown that the protein expression of chromatin remodeler Daxx in high grade invasive urothelial carcinoma of the bladder and in its preinvasive phases changed through quantitative immunohistochemical analysis [ 19 ]. Which effects have Daxx in the progress of cervical cancer induced by HR-HPVs?…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that in neurons, the function of Daxx varies according to its localization: for example, when Daxx is located in the nucleus, it is antiapoptotic, whereas when it is localized in the cytoplasm, it is proapoptotic . Numerous studies have been conducted examining the expression of, or mutations in, Daxx in tumor tissues, such as in oral cancer, pancreatic neuroendocrine tumors, urothelial carcinoma, prostate cancer, and ovarian cancer amongst others . In tumor cells, Daxx is mainly located in the nucleus and is considered as a cancer‐promoting factor.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, strong DAXX expression is linked to high Gleason score and increased cell proliferation index, suggesting that DAXX can serve as an independent prognosticator in PCa (8). Similarly to PCa, immunohistochemical analysis of DAXX in high grade urothelial carcinoma shows increased expression compared with normal urothelium (9). Likewise, increased DAXX expression in diffuse large B-cell lymphoma correlates with poor patient survival (10).…”
mentioning
confidence: 99%